Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Let's solve the equation [tex]\(1 - 2x - 1 = -10\)[/tex] step by step.
Firstly, simplify the left-hand side of the equation:
[tex]\[1 - 2x - 1 = -10\][/tex]
Notice that [tex]\(1 - 1\)[/tex] simplifies to 0, so we are left with:
[tex]\[-2x = -10\][/tex]
Next, we want to solve for [tex]\(x\)[/tex]. To do this, we need to isolate [tex]\(x\)[/tex]. Divide both sides of the equation by [tex]\(-2\)[/tex]:
[tex]\[ x = \frac{-10}{-2} \][/tex]
Simplify the fraction:
[tex]\[ x = 5 \][/tex]
Therefore, the solution to the equation [tex]\(1 - 2x - 1 = -10\)[/tex] is [tex]\(x = 5\)[/tex].
So, the correct answer is:
B. [tex]\(x = 5\)[/tex]
Firstly, simplify the left-hand side of the equation:
[tex]\[1 - 2x - 1 = -10\][/tex]
Notice that [tex]\(1 - 1\)[/tex] simplifies to 0, so we are left with:
[tex]\[-2x = -10\][/tex]
Next, we want to solve for [tex]\(x\)[/tex]. To do this, we need to isolate [tex]\(x\)[/tex]. Divide both sides of the equation by [tex]\(-2\)[/tex]:
[tex]\[ x = \frac{-10}{-2} \][/tex]
Simplify the fraction:
[tex]\[ x = 5 \][/tex]
Therefore, the solution to the equation [tex]\(1 - 2x - 1 = -10\)[/tex] is [tex]\(x = 5\)[/tex].
So, the correct answer is:
B. [tex]\(x = 5\)[/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.